UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MAYANA (Coleus atropurpureus [L] Benth) TERHADAP Staphylococcus aureus, Escherichia coli DAN Pseudomonas aeruginosa SECARA IN-VITRO - Mpila, Deby; Fatimawali, Fatimawali; Wiyono, Weny (PHARMACON, 2012)
The aims of this research were to study antibacterial activity, effective concentration and effect ofincreasing concentrations of ethanolic extract from mayana leaf (Coleus atropurpureus [L] Benth) onbacteria growth inhibition of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa.Extraction was done by maceration using ethanol 96%. Antibacterial activity test was done by usingpitting method, Kirby and Bauer agar difussion with modification. The result was analyzed by Oneway anova, followed by Duncan test. The result showed that extract concentrations (5, 10, 20, 40 and80%) possess bacterial inhibition activity. Extract concentrations (20, 40 and 80%) were effectivelyinhibit S. aureus growth and on effective concentration to inhibit E. coli were at 10, 20, 40 and 80%,while for P. aeruginosa were at 5, 10, 20, 40 and 80% extracts. The increase concentrations ofmayana extract shows high inhibition diameter of bacterial growth.Keywords : Antibacterial activity, Coleus atropurpureus [L] Benth, pathogen bacterial, agar difussionmethod